Fabrication and characterization of PVA/starch fibre using electrospinning technique - Nurul Farhana, Ahmad (2017)
In this research the polyvinyl alcohol (PVA) and starch are synthesized for the fabrication of fibre using electrospinning method. The fabrication of fibre for this research were prepared using four different ratio which were 100:0, 80:20, 60:40 and 50:50 of PVA/starch. The weight percent for the PVA and starch were 15wt% respectively. The obtained fibre were observed under the Scanning Electron Microscope (SEM) for the determination of the average diameter. The average diameter obtained for the four samples are 290.18 ± 26.24, 202.19 ± 37.75, 142.43 ± 25.96, 64.80 ± 8.26 respectively. For the TGA analysis, the first region of degradation is due to the loss of water content in the sample while the second and the third region is the decomposition of the main chemical chain and the decomposition of the main ring. The bond that had been detected in the sample tested are the O-H stretching, the C-H bending of CH2 and the C-O-C bond. The viscosity obtained from the conducted test were 3337 cP, 3959 cP, 1284 cP and 82 cP for respectively. The conclusion that can be made is the 60:40 of the PVA:starch sample produced the best fiber based on the observation on the morphology, thermal properties and chemical properties.